Convulsion Due To Use Imipramine: A Case Report - Taşkın, Gökmen; Çağan, Eren; Kaya, Avni; Başaranoğlu, Murat; Çaksen, Hüseyin (Fırat University, 2012)
An eight-year-old girl patient was admitted to hospital with generalized tonic-clonic seizure without fever. It was established from the patient's medical history that she was using imipramine 10 mg (0.41 mg/kg/day) for a duration of 20 days for enuresis nocturna. There was no specialty in the personal or family history. Her physical examination was normal. The serum electrolytes, liver function tests, renal function tests and brain magnetic resonance imaging were normal. The patient's seizure was considered to be linked to imipramine. Imipramine was stopped. The patient is being follow-up for six months without receiving anticonvulsant therapy. With this case, we would like to emphasize that imipramine could have caused the convulsion.

Sekiz yaşında kız hasta ateşsiz dönemde jeneralize tonik klonik nöbet geçirme şikayetiyle getirildi. Hikayesinden hastanın 20 gündür enürezis nokturna nedeniyle imipramin tablet 10 mg/gün (0.41 mg/kg/gün) kullandığı öğrenildi. Özgeçmişi ve soy geçmişinde özellik yoktu. Fizik muayenesi normal idi. Serum elektrolitleri, karaciğer ve böbrek fonksiyon testleri, beyin magnetik rezonans görüntülemesi normaldi. Hastanın nöbetinin imipramine bağlı olduğu kabul edildi ve imipramin kesildi. Hasta halen antikonvülsan tedavi almaksızın 6 aydır takip edilmektedir. Bu vaka dolayısıyla imipraminin konvülsiyon yapabileceğini vurgulamak isteriz.
İmipramin Kullanımına Bağlı Konvülsiyon Olgusu